Artificial intelligence in scientific writing - Chirichela, Isabele Alves; Mariani, Alessandro Wasum; Pêgo-Fernandes, Paulo Manuel (São Paulo Medical Journal, 2025)
Artificial intelligence (AI) has long fascinated humanity and has been vividly depicted in several movies, such as “2001: A Space Odyssey” with HAL 9000 and “The Terminator” with Skynet. The topic has gained even more traction in recent years, both in the media and everyday life with the advent of tools such as ChatGPT (Open AI), which was launched in November 2022. These AI applications are now utilized for a wide range of tasks, from seeking travel advice to generating intricate mathematical tables for economic studies. In this brief editorial, we will explore an AI application that significantly impacts the quality and volume of both general and medical science: the use of AI in scientific writing. According to ChatGPT, scientific writing “is a writing style used to present research information and results clearly, concisely, and accurately, following specific rules and structures. It is essential for the dissemination of scientific knowledge, enabling researchers, professionals, and the general population to understand, evaluate, and replicate studies and experiments”.